Kontribusi Antara Kekuatan Otot Lengan Terhadap Keterampilan Servis Bawah Dalam Permainan Bola Voli Di SMA Negeri 4 Seluma - Sujito, Tedi; Putra, Dwingki Marta; Astuty, Lina Tri (Educative Sportive, 2025)
This study aims to determine the contribution between arm muscle strength to lower service skills in volleyball games at SMP Negeri 4 Seluma. This type of research is correlational research. The research sample totalled 20 people. The instruments used in this study were the full up test and the lower serve test in volleyball games. Where the results of the contribution of arm muscle strength to the lower serve test were 90.17%. With the discovery of a significant contribution of arm muscle strength to the skill of serving down in a volleyball game at SMP Negeri 4 Seluma, the strength of the arm muscles to the lower serve test is 90.17%.4 Seluma, then arm muscle strength can be used as a tool to predict lower serve skills in volleyball games.